2021
DOI: 10.1002/rev3.3301
|View full text |Cite
|
Sign up to set email alerts
|

Physical education teacher motivation: A conceptual review and reconceptualisation

Abstract: Accomplishing the goal of physical education requires a motivated teaching force. The goals of this article are to (a) provide a theoretical perspective that physical education teacher motivation is contextually constructed in close relation with their job demands and recourses, and (b) articulate a reconceptualised theoretical platform for future research based on the theoretical perspectives of extrinsic motivation and the job demand–job resource model. A literature search was conducted and followed by a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…washing out of best practices; Richards et al, 2018a). Motivated teachers who feel psychologically and emotionally stable are better able to meet the needs of their students while still addressing learning objectives (Zhang, 2021). While not all teachers report strong perceptions of marginality, it has continuously been reported as one of the most significant barriers impacting teacher motivation and well-being in PE for several decades (Gaudreault et al, 2018; Laureano et al, 2014; Lux and McCullick, 2011; Richards et al, 2017; Templin, 1989; Woods and Lynn, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…washing out of best practices; Richards et al, 2018a). Motivated teachers who feel psychologically and emotionally stable are better able to meet the needs of their students while still addressing learning objectives (Zhang, 2021). While not all teachers report strong perceptions of marginality, it has continuously been reported as one of the most significant barriers impacting teacher motivation and well-being in PE for several decades (Gaudreault et al, 2018; Laureano et al, 2014; Lux and McCullick, 2011; Richards et al, 2017; Templin, 1989; Woods and Lynn, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Self-determination theory (SDT; Ryan & Deci, 2017) is a broad theoretical model for the study of motivation, which is receiving a growing attention to explain the influence of motivational experiences in initial PE teacher education (Zhang, 2021). This notwithstanding, no previous studies to date were found to analyze the distinctive roles that pre-service PE teachers' basic psychological need satisfaction and motivation may perform in their academic engagement.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study was to identify the role of cognitive factors and self-efficacy in innovation in physical education in the context of China. It is noted that the earlier literature is silent about the critical role of cognitive factors and self-efficacy in innovation in physical education in the context of China ( Zhang, 2021 ). It is observed that physical education plays a critical role in the mental and physical development of people to the advanced level.…”
Section: Introductionmentioning
confidence: 99%